Crossroads and cultures a history of the world's peoples - Smith, Bonnie G.; Van de Mieroop, Marc; Von Glahn, Richard; Lane, Kris E. (Bedford/St. Martin's, 2012)
The ancient world, from human origins to 500 C.E. -- The formation or regional societies, 500-1450 C.E. -- The early modern world, 1450-1750 -- The world from 1750 to the present.